Platelet Rich Plasma in the Treatment of Bisphosphonate-Related Osteonecrosis of the Jaw: Personal Experience and Review of the Literature. (10th June 2014) - Longo, F.; Guida, A.; Aversa, C.; Pavone, E.; Di Costanzo, G.; Ramaglia, L.; Ionna, F.
Abstract : Bisphosphonates (BPs) are a class of synthetic drugs commonly used to treat bone metastasis and various bone diseases that cause osseous fragility (such as osteoporosis). Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a common complication in patients who received BPs, especially intravenously. Recently, osteonecrosis of the jaw (ONJ) caused by chemotherapeutic not belonging to BPs drug class has been reported. For this reason, it has been proposed recently to rename BRONJ in antiresorptive agents related osteonecrosis of the jaw (ARONJ), to include a wider spectrum of drugs that may cause osteonecrosis of the jaw. The most debated topic about ARONJ/BRONJ is therapy. The most adequate procedure is far from being standardized and prevention seems to play a pivotal role. In our study, we considered 72 patients with BRONJ with nonsurgical therapy, surgical therapy, and surgical therapy with platelet rich plasma (PRP) gel to evaluate its therapeutic effect in promoting ONJ wounds healing. Good results showed by PRP in improving wound healing give away to case-control randomized studies that could give definitive evidence of its effectiveness.